Islamic Water Jurisprudence and Sustainable Development: A Maqāṣid Analysis of Muhammadiyah’s Water Fiqh in Light of SDGs 6 - Kholil Muttaqin; Ahmad Nubail; Indah Puji Lestari; Fityan Amanu; Fathan Qoriba (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
Muhammadiyah’s Water Jurisprudence provides a faith-based framework for sustainable and equitable water governance. This study examines its normative foundations through the lens of maqāṣid al-sharī‘ah and its relevance to Sustainable Development Goal 6 (SDG 6). Using a qualitative normative approach based on document analysis, the study finds that it integrates the objectives of ḥifẓ al-nafs, ḥifẓ al-māl, ḥifẓ al-nasl, and ḥifẓ al-bī’ah, which closely align with the targets of SDG 6, including safe water access, water quality improvement, efficient water use, and ecosystem protection. The study concludes that Muhammadiyah’s Water Jurisprudence provides a strategic Islamic framework for advancing sustainable water governance.